Impact of feeding dried distillers’ grains with solubles diet on microbiome and metabolome of ruminal and cecal contents in Guanling yellow cattle - Song, Chun; Zhang, Tiantian; Xu, Duhan; Zhu, Mingming; Mei, Shihui; Zhou, Bijun; Wang, Kaigong; Chen, Chao; Zhu, Erpeng; Cheng, Zhentao (Frontiers in Microbiology, 2023)
Dried distillers' grains with solubles (DDGS) are rich in nutrients, and partially alternative feeding of DDGS effectively reduces cost of feed and improves animals' growth. This study aimed to explore the effect of feeding cattle with a basal diet (BD) and a Jiang-flavour DDGS diet (replaces 25% concentrate of the diet) on microbiome and metabolome of ruminal and cecal contents in Guanling yellow cattle. The results showed that the ruminal and cecal contents shared the same dominance of Bacteroidetes, Firmicutes and Proteobacteria in two groups. The ruminal dominant genera were Prevotella_1, Rikenellaceae_RC9_gut_group, and Ruminococcaceae_UCG-010; and the cecal dominant genera were Ruminococcaceae_UCG-005, Ruminococcaceae_UCG-010, and Rikenellaceae_RC9_gut_group. Linear discriminant analysis effect size analysis (LDA > 2, P < 0.05) revealed the significantly differential bacteria enriched in the DDGS group, including Ruminococcaceae_UCG_012, Prevotellaceae_UCG_004 and Anaerococcus in the ruminal contents, which was associated with degradation of plant polysaccharides. Besides, Anaerosporobacter, Anaerovibrio, and Caproiciproducens in the cecal contents were involved in fatty acid metabolism. Compared with the BD group, 20 significantly different metabolites obtained in the ruminal contents of DDGS group were down-regulated (P < 0.05), and based on them, 4 significantly different metabolic pathways (P < 0.05) were enriched including "Linoleic acid metabolism", "Biosynthesis of unsaturated fatty acids", "Taste transduction", and "Carbohydrate digestion and absorption". There were 65 significantly different metabolites (47